(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Typhoid fever is endemic fever in many countries of the world. Typhoid fever (TF) is still an important health problem in many developing countries. The incidence of the diseases is estimated about 900 cases per lakh population per year. The diseases is characterised by constant fever, headache, constipation and diarrhoael. The mode of transmission is contaminated food and water especially in rainy season. All age group and sexes are equally susceptible to the infection. Animals are also suffers of this diseases. Salmonella enteric a serotype type causes Typhoid fever. The article discusses and summarizes important effect of vectors in particular season. Here I will also through light on expost-facto of the diseases and its treatment. This review will let the readers to have a particular concern of the Salmonella safety.